2019
DOI: 10.1039/c8ce01851k
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the π-hole donor ability of iodopentafluorobenzene – a conventional σ-hole donor for crystal engineering involving halogen bonding

Abstract: This study is the first recognition of iodopentafluorobenzene's π-hole donor ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 104 publications
1
31
0
Order By: Relevance
“…20a-c). [148][149][150] The combined computational and experimental results led them to conclude that ipfb is not only a σ-hole donor for halogen bonding, but also exhibits π-hole donor properties. The authors also identified the PtCl 4 2− anion as a potent squareplanar subunit for halogen-bonded supramolecular architectures (Fig.…”
Section: Crystengcomm Highlightmentioning
confidence: 99%
“…20a-c). [148][149][150] The combined computational and experimental results led them to conclude that ipfb is not only a σ-hole donor for halogen bonding, but also exhibits π-hole donor properties. The authors also identified the PtCl 4 2− anion as a potent squareplanar subunit for halogen-bonded supramolecular architectures (Fig.…”
Section: Crystengcomm Highlightmentioning
confidence: 99%
“…Consequently,m etal centers with increased nucleophilicity of the outerd z 2 Pt II orbitals might behave as synthons for XB assembly involving metal centers. As shd onors we employed two symmetric iodoperfluoroarenes ( Figure 2) that are rather commonly applied for XB crystal engineering( for statistics of their usage,s ee our recent works [39,40] ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cooperativity, either positive (synergy) or negative (anti‐synergy) is a very important phenomenon in many areas of chemistry 53–64 . Recently, Kukushkin and coworkers 57–64 have observed the existence of noncovalent interactions (hydrogen/halogen/chalcogen/π‐hole bonds) by X‐ray diffraction, investigated the cooperativity between them theoretically by DFT calculations followed by QTAIM analysis, and confirmed experimentally by combined FTIR, HRESI‐MS, 1 H NMR, and diffusion coefficient NMR measurements.…”
Section: Resultsmentioning
confidence: 94%